A note on regulatory responses to COVID-19 pandemic: Balancing banks’ solvency and contribution to recovery - Bitar, Mohammad; Tarazi, Amine (Journal of Financial Stability, 2022)
We discuss the implications on banks and the economy of prudential regulatory intervention to soften the treatment of non-performing exposures (NPEs) and ease bank capital buffers. We apply these easing measures on a sample of Globally Systemically Important Banks (G-SIBs) and show that these banks can play a constructive role in sustaining economic growth during the COVID-19 pandemic. In addition, an empirical analysis shows that prudential regulatory responses to COVID-19 along with high regulatory capital and low non-performing loans ratios are positively associated with economic growth. Thus, banks should maintain high capital ratios in the medium-term horizon to absorb future losses, as the effect of COVID-19 on the economy might take time to fully materialize.